Writing and grammar : communication in action, Ruby Level - Carrol, Joyce Armstrong; Wilson, Edward E.; Forlini, Gary (Upper Saddle River, New Jersey : Prentice-Hall, 2001)
Writing is one of the most powerful communication tools you will use today and for the rest of your life. You will use it to share your thoughts and ideas with others and even to communicate with yourself.
Part1. Writing -- Part2. Grammar, Usage, and Mechanics -- Part3. Academic and Workplace Skills .
Includes index.
Keywords: LANGUAGE ARTS